RANCANG BANGUN RODA TANPA UDARA (AIRLESS TYRE) UNTUK BEBAN MAKSIMAL KENDARAAN 40.000 N - Agus Mulyono; Ardyanto Darmanto; Gunarko Gunarko; Harnyoto Harnyoto; Farid Hendro Wibowo (TURBO [Tulisan Riset Berbasis Online], 2018)
Tyres without air / Airless Tyre do not have Tyres like most Tyres. Airless Tyre or airless Tyre designed to have a hexagonal / beehive spoke profile where this design will receive the same style as Tyres with air. Design of this airless Tyre using polyol and isocyanate material for flexible spoke wheel material, while the tread material uses natural rubber material added additive reinforcement.Before the spoke printing process is carried out a simulation to determine the strength of the material and the design that was designed, after which a mechanical test of rubber material was carried out to determine the physical strength of the material. After that, the printing process and the overall assembly are carried out and tested on the vehicle. Keywords:  Airless Tyre, Honey comb design,  Poliol and natural rubber.